The Effects of High Alkaline Fly Ash on Strength Behaviour of a Cohesive Soil - A. Binal (Advances in Materials Science and Engineering)
Contemporarily, there are 16 coal-burning thermal power plants currently operating in Turkey. This number is expected to rise to 46 in the future. Annually, about 15 million tons of fly ash are removed from the existing thermal power plants in Turkey, but a small proportion of it, 2%, is recyclable. Turkey’s plants are fired by lignite, producing Class C fly ash containing a high percentage of lime. Sulfate and alkali levels are also higher in Class C fly ashes. Therefore, fly ash is, commonly, unsuitable as an additive in cement or concrete in Turkey. In this study, highly alkaline fly ash obtained from the Yeniköy thermal power plants is combined with soil samples in different proportions (5%, 10%, 15%, 20%, and 25%) and changes in the geomechanical properties of Ankara clay were investigated. The effect of curing time on the physicomechanical properties of the fly ash mixed soil samples was also analyzed. The soil classification of Ankara clay changed from CH to MH due to fly ash additives. Free swelling index values showed a decrease of 92.6%. Direct shear tests on the cohesion value of Ankara clay have shown increases by multiples of 15.85 and 3.01 in internal friction angle values. The California bearing ratio has seen a more drastic increase in value (68.7 times for 25% fly ash mix).